Fire Hazard in Chattogram City Corporation Area: A Critical Analysis of Its Causes and Mitigation Measures - Hasan, Muhammad Rashidul; Kauser, Md. Rakibul Hasan; Ibrahim, Jihan (Frontiers in Sustainable Cities, 2021)
Fire, can have its origin either in natural or human activities resulting in death and/or property damage in a very short period of time. To develop fire hazard resilient cities proper attention should be given to all possible sections of development to facilitate the service. Chattogram city is the second largest city of Bangladesh. Due to rapid rate of urbanization and unplanned growth of urban centers; hazards like fire have become a menace for Chattogram City Corporation (CCC) area. So, the main objective of this research is to identify the nature of the fire hazard by analyzing the frequency and intensity over time through different checklist and analyzing the existing firefighting capacity. In addition to past fire incident records, direct questionnaire survey and expert opinion; have been done for primary data collection. Using GIS techniques, this study has found that 9 fire stations in CCC exhibit different frequency and intensity in different categories such as type of structure, land use, source of fire, damage and losses in last 5 years. The number of fire incidents increased from 200 to 675 which indicate that the frequency increased over time. Among 2514 fire accidents 47% occurred in residential areas and 27% occurred in commercial areas. Fire intensity also varies with seasonal variation over a year. Within last 5 years Chattogram City Corporation dealt with 17,90,91,200 BDT financial loss, 83 people got injured and 15 due to fire accidents. One the other hand, only 9 fire stations serve around 155 sq.km area and approximately 6 million people in CCC which 17 and 19 times larger than that of Bangkok and Oklahoma City. Finally, this data-driven approach and findings could help the emergency planners to take necessary steps for improving fire-fighting capability to ensure better fire safety and resiliency.